Intracranial Venous Alteration in Patients With Aneurysmal Subarachnoid Hemorrhage: Protocol for the Prospective and Observational SAH Multicenter Study (SMS) - Umana, Giuseppe E.; Tomasi, S. Ottavio; Palmisciano, Paolo; Scalia, Gianluca; Da Ros, Valerio; Al-Schameri, Rahman; Priola, Stefano M.; Brunasso, Lara; Giammalva, Giuseppe Roberto; Paolini, Federica; Costanzo, Roberta; Bonosi, Lapo; et al. (Frontiers in Surgery, 2022)
Background: Arterial vasospasm has been ascribed as the responsible etiology of delayed cerebral infarction in patients with aneurysmal subarachnoid hemorrhage (aSAH), but other neurovascular structures may be involved. We present the protocol for a multicenter, prospective, observational study focused on analyzing morphological changes in cerebral veins of patients with aSAH. Methods and analysis: In a retrospective arm, we will collect head arterial and venous CT angiograms (CTA) of 50 patients with aSAH and 50 matching healthy controls at days 0-2 and 7-10, comparing morphological venous changes. A multicenter prospective observational study will follow. Patients aged ≥18 years of any gender with aSAH will be enrolled at 9 participating centers based on the predetermined eligibility criteria. A sample size of 52 aSAH patients is expected, and 52 healthy controls matched per age, gender, and comorbidities will be identified. For each patient, sequential CTA will be conducted upon admission (day 0-2), at 7-10 days, and at 14-21 days after aSAH, evaluating volumes and morphology of the cerebral deep veins and main cortical veins. One specialized image collecting center will analyze all anonymized CTA scans, performing volumetric calculation of targeted veins. Morphological venous changes over time will be evaluated using the Dice coefficient and the Jaccard index and scored using the Boeckh–Behrens system. Morphological venous changes will be correlated to clinical outcomes and compared between patients with aSAH and healthy-controls, and among groups based on surgical/endovascular treatments for aSAH. Ethics and dissemination: This protocol has been approved by the ethics committee and institutional review board of Ethikkommission, SALK, Salzburg, Austria, and will be approved at all participating sites. The study will comply with the Declaration of Helsinki. Written informed consent will be obtained from all enrolled patients or their legal tutors. We will present our findings at academic conferences and peer-reviewed journals. Approved Protocol Version and Registration: Version 2, 09 June 2021.